Ecological crisis in Ukraine and its socio-economic impact - Stepanenko, Anatoliy (Human Geography Journal, 2014)
The essence and reasons of ecologic crisis in Ukraine are revealed, dependence of ecologic crisis on  level of ecologic security, increase of quantity of the sources of  ecologic insecurities. Considerable attention was paid to evaluation of level of ecologic situation and development of national ecologic system of Ukraine, its place according to these indicators among other countries in the world with EPI index. The reasons of aggravation of index of ecologic survey for Ukraine in 2010 and 2012 years were identified. Interconnection of economic and ecologic crises as well as place of Ukraine among worse world economies were revealed (fourth). It was shown, that Ukraine is the only country in the world, which economy in 2012 did not return to level of pre-crisis 2007 in 2012. It is defined increase of “predatory” treatment with nature and “ecologic nihilism”, so economic collapse and lack of real able-bodied state decisions support this situation. The social consequences of ecologic crisis are synergetics of ecologic and demographic crises, probable increase of ecologic migrations, influence of resettlement on ecologic safety, interrelation between society earnings and ecologic situation of environment. Influence of ecologic crisis on natural resources and environment is investigated, approaches of state policy as for ecologic crisis overcome are selected.